Saroglitazar and Hepano treatment offers protection against high fat high fructose diet induced obesity, insulin resistance and steatosis by modulating various class of hepatic and circulating lipids - Soumalya Sarkar (Elsevier, 2021)
Higher global prevalence of non-alcoholic fatty liver disease (NAFLD) is associated with obesity, steatosis, and insulin resistance (IR), and often progresses to steatohepatitis (NASH). Even after more than twenty years of research, there is still no FDA approved therapy for the treatment of fatty liver disease/NASH though, Saroglitazar - a dual PPAR α/γ agonist has been recently approved as a therapeutic option for the fatty liver disease in India. Hepatoprotective Ayurvedic formulations are widely used and are considered safe. In the present study, C57BL/6 male mice on HFHF diet for four weeks were treated with vehicle, Saroglitazar (3 mg/kg/po), and Hepano - a formulation of five herbs (200 mg/kg/po), at the human equivalent therapeutic doses for additional eight weeks. These animals were evaluated after 12 weeks for obesity, body mass index (BMI), systemic insulin resistance, hyperglycaemia, dyslipidaemia, and hepatic lipid accumulation. Differential liquid chromatography-mass spectrometry (LC-MS/MS) based lipidomics analysis demonstrated significant changes in the different class of lipids [phospholipids, sphingolipids, diglycerides and triglycerides (TG)] in HFHF fed group. The protective effects of both Saroglitazar and Hepano were evident against IR, obesity and in the modulation of different class of lipids in the circulation and hepatic tissue. Saroglitazar reduced TG as well as modulated phospholipids levels, while Hepano modulated only phospholipids, ceramides, oxidised lipids, and had no effect on hepatic or circulating TG levels in HFHF fed mice. In addition, in vitro studies using HepG2, THP1 and LX2 cells demonstrated safety of both the test substances where Hepano possess better anti-inflammatory as well as anti-fibrotic potential. Overall, Saroglitazar seems to be more efficacious than Hepano in the regimen used against HFHF induced IR, obesity, and dyslipidaemia.